Principals’ Teacher Management Strategies and Learners’ Academic Achievement in Public Secondary Schools in Kilifi Sub-County, Kenya - Kilwake , Everlyne; Okemasisi , Kinikonda; Aringo, Margaret (Journal of Education and Practice, 2023)
Purpose: Effective management of teachers in a school system plays an important role in facilitating students' academic achievement as they prepare for life opportunities. This study investigated the influence of the principals' teacher management strategies on students' academic achievement in Kilifi Sub-County, Kenya. The specific objectives of the research were: to assess whether principals' provision of incentives to teachers has effects on students' academic performance; to find out the extent to which principals' promotion of teachers' team work influences students' academic performance in public secondary schools in Kilifi Sub-County. Methodology: The study was guided by the Total Quality Management theory. A descriptive survey research design was adopted for the study. The study targeted secondary school principals, teachers, and students, Quality Assurance and Standards Officer and Teachers Service Commission County Director. Purposive sampling was used to select 10 public secondary schools, 10 principals, one Quality Assurance and Standards officer, and a County Director from Teacher Service Commission. Simple random sampling was used to select 90 out of 250 teachers. Proportionate sampling was adopted to select 306 out of 1300 students. Test - Retest Reliability scores of the teachers and students research instruments were 0.817 and 0.774 respectively. The researcher used questionnaires, interview guide and document analysis to collect data from different participants; students, teachers, Quality Assurance and Standards Officer and Teacher Service Commissions County Director. Quantitative data was analyzed using the Statistical Package for Social Science Software Version 23. Descriptive statistics such as frequencies and percentages were presented in the form of bar graphs, pie charts, and tables. Inferential statistics (correlation) were presented in the tables. Qualitative data was arranged into themes and recorded in the form of narratives and direct quotations. Findings: The findings of the study showed that though the teachers were given paid leave, over time bonuses, and gifts as incentives to improve their performance, they were not given opportunities for professional development which affected their performance. Further, the study established a weak teamwork spirit between the teachers and the principals. School principals did not include teachers in the decisions that affect them. The study concluded that teamwork provided opportunities for continuous improvement and led to higher rates of satisfaction among teachers. Unique Contribution to Theory, Policy and Practice: The study recommended that the principals give the teachers incentives such as professional development opportunities through workshops and seminars to enable them to acquire more skills. The study further recommended that the principals put in place measures that would enhance the quality of teamwork among teachers. This would enhance teachers' performance and learners' academic achievement in public secondary schools in Kilifi Sub-County, Kenya.